Participant observation - Spradley, J.P. James P Spradley (New York: Wadsworth Cengage learning, 1980)
This text is a follow up to Spradley's earlier ethnographic research handbook, The Ethnographic Interview, and guides students through the technique of participant observation to research ethnography and culture. Spradley also teaches students how to analyze the data they collect and write an ethnography.
Includes appendix, bibliographical references and index.
Keywords: Participant observation